CONSTRUCTING IDENTITY AND COMMUNALITY ON A SOCIAL MEDIA PLATFORM: An Exploration of #Igbotwitter Tweets - Udenze, Silas (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2022)
Social media have a burgeoning on our lives as they have become avenues for the exhibition of life experiences, and they also a variety of dimensions regarding our position in the online and offline social life. These factors make individuals play certain characters in the social arena. Expanding on Vogel et al.'s (2014) idea of "fulfilling belongingness", this paper explores to what extent Igbos in diaspora use the Twitter hashtag to construct the Igbo identity and how the Twitter hashtag #Igbotwitter reflects a complex transnational dialogue about Igbo identity markers in a globalized media landscape. Adopting an interpretive thematic analysis and Dowdall and Golden's (1989) method for image analysis, the study analyzed 47 #Igbotwitter tweets shared by diaspora Nigerians. The analysis revealed some overarching themes like "The Igbos as Business-Minded People", "Cultural/Traditional Enthusiast", among others. This study draws attention to how social media provide users with a unique space to address cultural and socio-economic discourse, reconstruct identities, and refute cultural misconceptions on a transnational level. It further highlights how the users attempt to preserve and protect the Nigerian Igbo identity and also fulfil a sense of belongingness in the current networked media environment. This study contributes to the literature on identity construction on digital platforms, and by implication points to the intentional and positive use of social media to promote culture on a global scale.  To cite this article (7th APA style): Udenze, S. (2022). Constructing identity and communality on a social media platform: an exploration of #igbotwitter tweets. Journal Communication Spectrum: Capturing New Perspectives in Communication 12(1), 11-28. http://dx.doi.org/https://doi.org/10.36782/jcs.v11i2.2120